Enhanced Photocatalytic Reduction of CO2 to CO through TiO2 Passivation of InP in Ionic Liquids. Issue 39 (27th July 2015) - Zeng, Guangtong; Qiu, Jing; Hou, Bingya; Shi, Haotian; Lin, Yongjing; Hettick, Mark; Javey, Ali; Cronin, Stephen B.
Abstract A robust and reliable method for improving the photocatalytic performance of InP, which is one of the best known materials for solar photoconversion (i.e., solar cells). In this article, we report substantial improvements (up to 18×) in the photocatalytic yields for CO2 reduction to CO through the surface passivation of InP with TiO2 deposited by atomic layer deposition (ALD). Here, the main mechanisms of enhancement are the introduction of catalytically active sites and the formation of a pn‐junction. Photoelectrochemical reactions were carried out in a nonaqueous solution consisting of ionic liquid, 1‐ethyl‐3‐methylimidazolium tetrafluoroborate ([EMIM]BF4), dissolved in acetonitrile, which enables CO2 reduction with a Faradaic efficiency of 99 % at an underpotential of +0.78 V. While the photocatalytic yield increases with the addition of the TiO2 layer, a corresponding drop in the photoluminescence intensity indicates the presence of catalytically active sites, which cause an increase in the electron‐hole pair recombination rate. NMR spectra show that the [EMIM]+ ions in solution form an intermediate complex with CO2−, thus lowering the energy barrier of this reaction.